Epithelioid hemangioma (Angiolymphoid hyperplasia with eosinophilia) in zosteriform distribution - Yuichi Kurihara; Hiroyoshi Inoue; Hiromaro Kiryu; Masutaka Furue (Wolters Kluwer Medknow Publications, 2012)
Epithelioid hemangioma (EH) or angiolymphoid hyperplasia with eosinophilia (ALHE) is an uncommon benign disease. We report an unusual case of EH (ALHE) that arose on the lower back in a zosteriform array. The presence of the characteristic histological appearance of plump endothelial cells with hobnail-like protrusions led to the diagnosis of EH (ALHE). Histological examination of the lesion also revealed the existence of arteriovenous shunts, the possible factor contributing to the pathogenesis of EH (ALHE).